Un cas du bricolage: le financement de la création de toutes petites entreprises par les femmes à Thiès (Sénégal). (2nd January 2023) - Ntep, Félix
Abstract: The debate on the funding of business creation focuses on the provision of funds by banks. Our study examines the financial behavior of eighteen women who set up small craft and commercial activities. It is based on a theoretical approach and on a qualitative methodology, which give a central place to the temporal and exploratory dimension in the understanding of the various interactions between the creators of the companies and their closer financial environment. The results of the study show a case of DIY. The latter is revealed in the ability of women to assign new objectives to financial resources, which they have mobilized from the banks of the financial system, mutual tontines, relatives and friends. This tinkering is a source of understanding for the State, the actors of the financial system and civil society, who participate in the renewal of the business park, in Thiès, in the Escale-Nord district, in Senegal.